Consultation between forensic and clinical pathologists for histopathology examination after forensic autopsy. (January 2021) - Cirielli, Vito; Bortolotti, Federica; Cima, Luca; De Battisti, Zeno; Del Balzo, Giovanna; De Salvia, Alessandra; Laposata, Chiara; Raniero, Dario; Vermiglio, Elisa; Portas, Margherita; Rodegher, Pamela; Ghimenton, Claudio; et al.
The magnitude of the diagnostic benefit conferred by performing histopathological examinations after medico-legal/forensic autopsies remains debatable. We have tried to address this issue by reviewing a series of histopathology referrals concerning medico-legal autopsies in real-world routine practice. We present an audit of the consultations provided to forensics by clinical pathologists at our institute between 2015 and 2018. Over this period, 493 post-mortem examinations were performed by forensic pathologists. Of these cases, 52 (11%) were referred for histopathology. Gross assessment was requested in 22/52 (42%) cases. Histopathology examination was performed on single organs in 15/52 (29%) cases, primarily on the lung and heart, whereas parenchymatous multi-organ analysis was carried out in 14/52 (27%) cases. Bone-marrow sampling was studied in 4/52 (8%) cases. Immunohistochemistry was needed in 16/52 (31%) cases, special stains in 9/52 (21%) cases and molecular analysis in 4/52 (8%) cases. Focusing on technical processes, standard methodology on pre-analytical procedures was changed in 10/52 (19%) cases in order to answer specific diagnostic questions. We showed that although most of the time the diagnosis is clear by the end of dissection on the basis of the macroscopic findings, histopathology can provide, modify or confirm the cause of death in many medico-legal/forensic cases. Therefore, it is desirable that forensic pathologists and clinical pathologists establish robust working relationships in a cooperative environment. We conclude that it is important to implement guidelines based on real-world routine practice in order to identify cases where histopathology can provide useful contributions, which in our experience applied to 11% of forensic cases.